PO 18019 - Osteonecrosis of the intermediate cuneiform bone: case report - Nunes, Gustavo Araújo; Oliveira Junior, Otaviano de; Maciel, Bruno Braga; Marcatti, Mateus Martins; Bertolini, Fabricio Melo (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Osteonecrosis is a disease that rarely affects foot bones. When present, it is more commonly found in the talus and navicular bones. Cases of osteonecrosis of the intermediate cuneiform bone are extremely rare, and after a literature review, we found 5 reported cases, all in pediatric patients. Objective: The objective of this study is to report a case of an adult patient with osteonecrosis of the intermediate cuneiform bone that was resistant to conservative treatment, for which we proposed a surgical approach. Results: The patient underwent surgical treatment and showed excellent clinical and radiographic progression, with significant improvements in the American Orthopedic Foot and Ankle Society (AOFAS) score and in the pain visual analog scale. He rated the outcome as excellent and reported that he would undergo the procedure again. Conclusion: The authors present a rare case of an adult patient with osteonecrosis of the intermediate cuneiform bone that was surgically treated with decompression and bone grafting and had a good outcome.